Analysis Of Company Growth and Liquidity on Profitability (Financial study on property and real estate sub-sectors listed on the on the IDX) - Syaban, Agil; Ramdan, Asep M.; Jhoansyah, Dicky (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
If the company decides to set a large amount of working capital, it is likely that the liquidity level will be maintained but the opportunity to earn a large profit will decrease, which in turn has an impact on decreasing profitability. The purpose of this study is to determine company growth, company liquidity, and profitability in the property and real estate sub-sector listed on the IDX for the period 2019 - 2021. The research methods used in this study are associative and descriptive methods with a quantitative approach. The population in this study is the property and real estate sub-sector listed on the IDX for the period 2019 - 2021, with the number of samples used in the study, namely 20 manufacturing companies. The data collection techniques used in this research are documentation and literature study. The data analysis techniques used in this study are Descriptive Statistical Techniques, Multiple Correlation Coefficients, Coefficient of Determination, Simultaneous Test, Multiple Linear Regression, and Hypothesis Testing. The results of this study indicate that the statistical test results show the tcount of the variable Company growth (X1) of 2.248> 2.000995 then Ho is rejected and Ha is accepted. It can be seen that company growth has a significant effect on profitability. Based on the results of statistical tests, the tcount of the Liquidity variable (X2) is 2.018> 2.000995, so Ho is rejected and Ha is accepted. It can be known that liquidity has a significant effect on profitability